Genotypic Males Play an Important Role in the Creation of Genetic Diversity in Gynogenetic Gibel Carp - Zhao, Xin; Li, Zhi; Ding, Miao; Wang, Tao; Wang, Ming-Tao; Miao, Chun; Du, Wen-Xuan; Zhang, Xiao-Juan; Wang, Yang; Wang, Zhong-Wei; Zhou, Li; Li, Xi-Yin; et al. (Frontiers in Genetics, 2021)
Unisexual lineages are commonly considered to be short-lived in the evolutionary process as accumulation of deleterious mutations stated by Muller’s ratchet. However, the gynogenetic hexaploid gibel carp (Carassius gibelio) with existence over 0.5 million years has wider ecological distribution and higher genetic diversity than its sexual progenitors, which provides an ideal model to investigate the underlying mechanisms on countering Muller’s ratchet in unisexual taxa. Unlike other unisexual lineages, the wild populations of gibel carp contain rare and variable proportions of males (1%-26%), which are determined via two strategies including genotypic sex determination and temperature-dependent sex determination. Here, we used a maternal gibel carp from strain F to be mated with a genotypic male from strain A+, a temperature-dependent male from strain A+, and a male from another species common carp (Cyprinus carpio), respectively. When the maternal individual was mated with the genotypic male, a variant of gynogenesis was initiated, along with male occurrence, accumulation of microchromosomes, and creation of genetic diversity in the offspring. When the maternal individual was mated with the temperature-dependent male and common carp, typical gynogenesis was initiated that all the offspring showed the same genetic information as the maternal individual. Subsequently, we found out that the genotypic male nucleus swelled and contacted with the female nucleus after fertilization although it was extruded from the female nucleus eventually, which might be associated with the genetic variation in the offspring. These results reveal that genotypic males play an important role in the creation of genetic diversity in gynogenetic gibel carp, which provides insights into the evolution of unisexual reproduction.